CASE OF SEVERE JUVENILE-ONSET ANKYLOSING SPONDYLITIS IN A PATIENT WITH RECURRENT UVEITIS - K. A. Gamayunova; A. P. Rebrov; Y. V. Galstyan; T. G. Kamenskikh (Архивъ внутренней медицины, 2019)
The objective of the study — to describe a clinical case of severe juvenile-onset ankylosing spondylitis in a patient with persistently recurrent uveitis.Materials and methods. Patient I., 43 years old, was constantly monitored since the age of 26 at the Department of Reumatology of the Saratov Regional Clinical Hospital with ankylosing spondylitis, an early onset of exstra-skeletal manifestations in the form of frequently recurring uveitis, and a number of complications.Results. Some complications, which caused complete loss of vision in both eyes, occurred during the observation period due to poor treatment adherence.Conclusion. The clinical observation presents some features of the disease, course treatment and the development of complications in the patient with ankylosing spondylitis and recurrent uveitis.